Game of thrones to learn science. an experience with spanish pre-service science teachers - Franco-Mariscal, Antonio Joaquín; Hierrezuelo-Osorio, José Manuel; Cano-Iglesias, María José (My University, 2019)
The most consumed media in Spain in 2018 was television, with fiction series being the favourite among young people. This work shows how this medium can be used as an educational resource in science education by studying problematic situations of interest, presenting the results of an experience carried out with 52 pre-service science teachers (PST) who worked with the television show Game of Thrones in an educational innovation subject of the Master’s Degree in Secondary Education Teaching at the University of Málaga (Málaga, Spain). The PSTs were asked to watch several sequences from the TV show, from which they had to select frames and propose driven questions on physics, chemistry, biology and geology for secondary school students, explaining how to approach them in the classroom. The proposals were categorized by scientific disciplines according to the contents used and the explanations given. The experience was assessed from a questionnaire that included items about the learning achieved, the educational possibilities of the resource and the emotions felt. On their learning, they highlighted how a playful resource can be converted into an educational resource to motivate students. The resource was well received with a score of 8.53 out of 10, increasing the average knowledge of the PSTs of their educational possibilities from 1.96 to 4.54 (on a scale of 5 points) before and after the experience. The PSTs highlighted interest, satisfaction and concentration as the main emotions felt during the experience. This study is considered novel since it applies this strategy to teachers in training, analysing their capacity to teach and their perceptions. Finally, it should be noted that the educational use of television as a resource in the classroom allows us to connect scientific and school knowledge, can motivate disinterested students and provide a pedagogical tool that enhances instruction.
Keywords: Innovación educativa; teaching innovations; initial teacher education (pre-service); science education